2000
DOI: 10.2134/jeq2000.00472425002900020028x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Perchlorate in Ground Water with a Flow‐Through Bioreactor

Abstract: The bacterium, perc1ace, has been shown to reduce perchlorate to less than the detection limit of 0.004 mg L−1 when grown on acetate under anaerobic conditions. In batch studies, the presence of nitrate does not significantly hinder the reduction of perchlorate. The ability of perclace to remove nitrate and perchlorate from ground water in a flow‐through system is described in this study. Celite‐packed columns of 300 ml were used to demonstrate the removal of perchlorate from ground water. At a flow rate of 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Isotopic data show the effects of evaporation in that the meteoric water trend is not observed; rather data follow along a trajectory below the meteoric water trend having a slope of about 5 instead of 8. Ratios of 18 O/ 16 O and 2 H/ 1 H are more variable in the summer, because of greater precipitation and generally more intense evaporation compared to the late fall and winter. Considering the limited rainfall that occurred over the period that perchlorate concentrations were decreasing in Wintersmith Lake (Figure 3) and the overall evaporitic trend indicated by the isotopic data (Figure 4), dilution is not expected to be an important factor in lowering perchlorate levels in this system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isotopic data show the effects of evaporation in that the meteoric water trend is not observed; rather data follow along a trajectory below the meteoric water trend having a slope of about 5 instead of 8. Ratios of 18 O/ 16 O and 2 H/ 1 H are more variable in the summer, because of greater precipitation and generally more intense evaporation compared to the late fall and winter. Considering the limited rainfall that occurred over the period that perchlorate concentrations were decreasing in Wintersmith Lake (Figure 3) and the overall evaporitic trend indicated by the isotopic data (Figure 4), dilution is not expected to be an important factor in lowering perchlorate levels in this system.…”
Section: Resultsmentioning
confidence: 99%
“…Perchlorate-reducing organisms can use a variety of organic carbon substrates as electron donors, such as glucose, acetate, vegetable oils, and natural organic carbon compounds present in soils and sediments (6,8,14,15). Biological transformation of perchlorate has been successfully utilized for drinking water treatment (16)(17) and for in situ groundwater remediation (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, a carbon source (electron donor) is required to facilitate perchlorate reduction, either as soil organic carbon (Tipton et al 2003), carbon dioxide (Zheng et al 2002), a carboxylic acid (e.g., acetate; Herman and Frankenberger 1999;Giblin et al 2000;Logan et al 2001;Kim and Logan 2001), or even the co-contaminant nitroglycerin (Attaway 1994). Perchlorate reduction requires molybdenum in some microbe strains (Chaudhuri et al 2002).…”
Section: Perchlorate and Chlorate Saltsmentioning
confidence: 99%
“…Perchlorate reduction requires molybdenum in some microbe strains (Chaudhuri et al 2002). Many studies report sequential or simultaneous reduction of nitrate and perchlorate under anaerobic conditions by different microbe strains or communities (Herman and Frankenberger 1999;Giblin et al 2000;Okeke et al 2002;Chaudhuri et al 2002;Tipton et al 2003). Anaerobic perchlorate reduction is inhibited by nitrite, which appears as a nitroglycerin transformation product during propellant manufacture (Attaway 1994).…”
Section: Perchlorate and Chlorate Saltsmentioning
confidence: 99%
“…Several studies have shown that biological treatment is an effective technology to remove perchlorate from drinking water (Brown et al, 2002;Giblin et al, 2000;Herman and Frankenberger, 1999;Min et al, 2004). For example, for a typical groundwater concentration of 50 μg/L, biologically active carbon (BAC) fixed bed reactors consistently removed perchlorate to below 2 μg/L (Brown et al, 2002(Brown et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%